2018
DOI: 10.1242/jeb.177147
|View full text |Cite
|
Sign up to set email alerts
|

Paralytic hypo-energetic state facilitates anoxia tolerance despite ionic imbalance in adultDrosophila melanogaster

Abstract: Oxygen limitation plays a key role in many pathologies; yet, we still lack a fundamental understanding of the mechanisms responsible for variation in anoxia tolerance. Most vertebrate studies suggest that anoxia tolerance involves the ability to maintain cellular ATP despite the loss of aerobic metabolism. However, insects such as adult are able to survive long periods of anoxia (LT: ∼8 h) in a hypo-energetic state characterized by low [ATP]. In this study, we tested for possible mechanisms that allow adults t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…ATP concentrations tend to decrease even further with prolonged anoxia as has been shown in L. migratoria (Weyel and Wegener, 1996) and D. melanogaster (Campbell et al, 2018). It has been suggested that anoxic mortality only occurs when ATP levels are close to zero and anoxic survival may therefore involve some ability to regulate/maintain ATP at a low but non-zero level (Campbell et al, 2018). The low ATP levels are likely to reduce the activity of ion-motive ATPases, resulting in a gradual loss of ion homeostasis during anoxia.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…ATP concentrations tend to decrease even further with prolonged anoxia as has been shown in L. migratoria (Weyel and Wegener, 1996) and D. melanogaster (Campbell et al, 2018). It has been suggested that anoxic mortality only occurs when ATP levels are close to zero and anoxic survival may therefore involve some ability to regulate/maintain ATP at a low but non-zero level (Campbell et al, 2018). The low ATP levels are likely to reduce the activity of ion-motive ATPases, resulting in a gradual loss of ion homeostasis during anoxia.…”
Section: Introductionmentioning
confidence: 69%
“…fruitfly larvae; see Callier et al, 2015), enter a neuromuscular coma when exposed to anoxia (Wegener, 1993;Rodgers et al, 2010) and longer anoxic exposures reduce survival and increase the time it takes for insects to recover from anoxia (Wu et al, 2002;Lighton and Schilman, 2007). The lack of aerobic ATP production disrupts ATP homeostasis, causing ATP concentrations to drop rapidly (Wegener, 1993;Hoback, 2012;Campbell et al, 2018). ATP concentrations tend to decrease even further with prolonged anoxia as has been shown in L. migratoria (Weyel and Wegener, 1996) and D. melanogaster (Campbell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mosquito larvae obtain gaseous oxygen from the water surface through a siphon on the posterior end of their abdomen, so sinking during cold stress may limit access to oxygen during a cold stress and cause systemic hypoxia. Like cold stress, anoxia has been demonstrated to cause disruptions of ion homeostasis leading to hyperkalemia in Drosophila (Campbell, Andersen, Overgaard, & Harrison, 2018), meaning an inability to access sufficient oxygen during chill coma may further contribute to ionic imbalance and injury in the cold in this aquatic insect. Alternatively, as the metabolic rate of ectotherms is strongly supressed during cold exposure, larvae may obtain sufficient oxygen from the surrounding water during cold stress to fuel metabolism and avoid the downstream consequences of hypoxia.…”
Section: Discussionmentioning
confidence: 99%